2019
DOI: 10.18203/2320-1770.ijrcog20190494
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of anemia during pregnancy and its association with adverse perinatal outcomes in Madhya Pradesh, India

Abstract: Background: The prevalence of anemia in India is increasing day by day and covers almost one third population. Anemia during pregnancy leads many perinatal complications such as miscarriage, abortion and still birth. So, the aim of the study was to determine prevalence of anemia during pregnancy and its association with adverse perinatal outcomes in region of Madhya Pradesh.Methods: The study population consisted of 15-49 years women of reproductive age group from the state Madhya Pradesh, India, which were ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…For instance, those anemic pregnant women were found more likely to develop antepartum and postpartum hemorrhage and abnormal puerperium especially infection [11,12]. It may also result in a miscarriage [13] and preterm delivery [14]. Anemia during pregnancy and breastfeeding affects not only mothers but also has an impact on their children.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, those anemic pregnant women were found more likely to develop antepartum and postpartum hemorrhage and abnormal puerperium especially infection [11,12]. It may also result in a miscarriage [13] and preterm delivery [14]. Anemia during pregnancy and breastfeeding affects not only mothers but also has an impact on their children.…”
Section: Introductionmentioning
confidence: 99%
“…In this study of "Prevalence of anemia during pregnancy and its association with adverse perinatal outcomes in Madhya Pradesh, India" by Divya Sinha concluded that There exists a direct correlation between the severity of anaemia and unfavourable perinatal outcomes during pregnancy. 14 In table no. 3 The majority of respondents are positively aware of nutrition and weight management, as well as their negative impact on pregnancy, while a minority are less or poorly aware of their harmful impacts.…”
Section: Discussionmentioning
confidence: 99%